The challenges of rainfed agricultural practices in Mali-redefining research agenda - A short communication - Zemadim, Birhanu (MedCrave Group Kft., 2016)
Mali is one of the least developed countries with an economy that relies heavily on rainfed cereal production. Rural communities are faced with extreme poverty as a result of unpredictable rainfall pattern and lack of appropriate agricultural intervention practices. Most agronomic practices in support of development in the past had emphasized farm-level productivity issues with limited scope for managing interactions among components and actors beyond the level of the farm. Several studies showed different techniques practiced at farm level to improve the agricultural productivity. However rural communities at large are unable to cope with the impacts of climate change and other shocks related to agricultural input supplies and market access. In this short communication paper recent findings related to the challenges of rainfed agricultural practices were discussed to inform policy makers, researchers and development practitioners to re-define approaches towards sustainable agricultural development. In addition new research agenda was discussed that aim to integrate interactions among components and actors beyond the level of the farm to improve rural resilience.